发动机前端附件驱动系统静动态性能设计计算软件 - 上官文斌; 杨嘉威; 冯骁 (Jixie chuandong)
EFEAD-Kit software is an automated analysis tool for evaluating static and dynamic characteristics of Engine Front End Accessory Drive（EFEAD） system.Introduction of the program including static design module and dynamic design module is proposed firstly.Then the characteristics of user interface and the function of EFEAD-Kit software are described.Finally,a generic EFEAD system is taken as a studying example,and its static and dynamic performance are calculated using the software and are compared with experiment.